Large perpendicular magnetic anisotropy of transition metal dimers driven by polarization switching of a two-dimensional ferroelectric In2Se3 substrate. Issue 36 (7th September 2022) - Qiao, Wen; Jin, Deyou; Mi, Wenbo; Wang, Dunhui; Yan, Shiming; Xu, Xiaoyong; Zhou, Tiejun
Abstract : Large perpendicular magnetic anisotropy (MA) is highly desirable for realizing atomic-scale magnetic data storage which represents the ultimate limit of the density of magnetic recording. Abstract : Large perpendicular magnetic anisotropy (MA) is highly desirable for realizing atomic-scale magnetic data storage which represents the ultimate limit of the density of magnetic recording. In this work, we study the MA of transition metal dimers Co–Os, Co–Co and Os–Os adsorbed on two-dimensional ferroelectric In2 Se3 (In2 Se3 -CoOs, In2 Se3 -OsCo, In2 Se3 -CoCo and In2 Se3 -OsOs) using first-principles calculations. We find that the Co–Os dimer in In2 Se3 -CoOs has a total magnetic anisotropy energy (MAE) of ∼40 meV. The MAE arising from the Os atom in In2 Se3 -CoOs is up to ∼60 meV. Such large MAE is attributed to the high spin–orbit coupling constant and the onefold coordination of the Os atom. In addition, perpendicular MA can be enhanced in In2 Se3 -CoOs and induced in In2 Se3 -OsCo, In2 Se3 -CoCo and In2 Se3 -OsOs by the ferroelectric polarization reversal of In2 Se3 . We demonstrate that the enlargement of exchange splitting of d xy /d x 2 − y 2 and d xz /d yz orbitals for Os atoms in In2 Se3 -OsOs, Co atom in In2 Se3 -CoOs and Os and Co atoms in In2 Se3 -OsCo is responsible for the increase of MAE; while, for the upper Co atom in In2 Se3 -CoCo and the Os atom in In2 Se3 -CoOs, the energy rise of the d z 2 orbital owing to the change of the crystal field effect by the reversal of ferroelectric polarization results in the increase of MAE.